STUDENTS’ ATTITUDE AND PERSONALITY TRAITS TOWARD ENGLISH LEARNING ACHIEVEMENTS - Meiriska Nirmala Dewi (TANJAK, 2021)
There are some factors that may influence students English learning achievements. They may be internal and external factors. This study focuses on internal factors of students which assumed affecting their English learning achievements; they are students’ attitude and personality traits. To find out the influence of students’ attitude and personality traits towards their English learning achievement, some theories and previous related research have been carried out. Based on the theories, people’ attitudes influence on how they behave, think, and respond to something. Besides, students’ personality traits are also assumed has influence to their English learning achievements. Goldberg (2001) proposes International Personality Item Pool (IPIP) to assess partcipants’ perception of personality traits. This study adopted questionnaires of IPIP about personality traits and provided another questionnaire about attitudes. Design of this study is a correlational research design which used simple and multiple regression analysis. The finding shows that there is significant influence of students’ attitude and personality traits towards their English learning achievements. Keywords: attitudes, personality traits, English achievements.